Implementasi Optical Character Recognition dan Text Similarity untuk Pelaporan Uang Muka Kerja - Susanty, Meredita; Megandi, Megandi; Setiawan, Erwin (Teknik Informatika Universitas Pamulang, 2024)
The request and accountability reporting of cash advances in companies are now widely supported by web-based applications. However, the process of verifying the completeness and consistency of expense receipts against financial reports is still performed manually by financial staff, which is time-consuming. This study aims to implement Optical Character Recognition (OCR) technology to extract text from payment receipts and match it with expenditure items in financial reports. This technology enables the automation of financial verification processes using a text similarity algorithm based on Levenshtein Distance. By implementing this system, the time required for financial report verification can be significantly reduced, allowing staff to focus on more strategic tasks. The system was tested by integrating the Veryfi OCR application with an API-based system to process payment receipts in various formats. The test results indicate that the system successfully identifies and matches transactions with a high accuracy rate. However, further development is needed to incorporate discount and tax calculations from payment receipts.